2011
DOI: 10.1194/jlr.m013615
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2-EP4 signaling suppresses adipocyte differentiation in mouse embryonic fibroblasts via an autocrine mechanism

Abstract: Adipogenesis is a crucial aspect in controlling body fat mass ( 1, 2 ). Acquisition of the mature adipocyte phenotype is a highly regulated process in which mesenchymal stem cells (MSC) undergo differentiation, resulting in both an increase in size and number of mature adipocytes in adipose tissue. Adipose tissue is important not only for energy storage but also as an endocrine organ that regulates energy homeostasis by secreting various adipokines, such as cytokines, chemokines, growth factors, and lipid medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…Finally, we found that mPGES-1 is responsible for the production of PGE 2 in adipocytes [60]. This result is consistent with results showing that treatment of mouse embryonic fibroblast (MEF) cells with PGE 2 for the first two days of adipocyte differentiation is enough to suppress adipocyte differentiation, with reduced expression of the PPAR γ 2 gene and reduced accumulation of intracellular lipids [43]. …”
Section: Suppression Of the Early Phase Of Adipogenesis By Pge2supporting
confidence: 84%
See 2 more Smart Citations
“…Finally, we found that mPGES-1 is responsible for the production of PGE 2 in adipocytes [60]. This result is consistent with results showing that treatment of mouse embryonic fibroblast (MEF) cells with PGE 2 for the first two days of adipocyte differentiation is enough to suppress adipocyte differentiation, with reduced expression of the PPAR γ 2 gene and reduced accumulation of intracellular lipids [43]. …”
Section: Suppression Of the Early Phase Of Adipogenesis By Pge2supporting
confidence: 84%
“…PGF 2 α and PGE 2 suppress the differentiation of adipocytes and exert their functions as antiadipogenic agents exert by acting through their specific FP [3741] and EP4 [42, 43] receptors, respectively. …”
Section: Repression Of the Early Phase Of Adipogenesis By Pgf2 αmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PGF 2α induces the production of anti-adipogenic PGE 2 and PGF 2α by triggering the PTGFR receptor/MEK/ERK cascade in 3T3-L1 cells [18]. PGE 2 also enhances the production of anti-adipogenic PGE 2 and PGF 2α in mouse embryonic fibroblasts [20].…”
Section: Resultsmentioning
confidence: 99%
“…PGI 2 is involved in the activation of preadipocytes to adipocytes through PGI 2 receptor [14], [15]. In contrast, PGF 2α and PGE 2 suppress the progression of adipogenesis [17], [18], [19], [20]. PGF 2α is synthesized by AKR1B3 in adipocytes and represses the early phase of adipogenesis by engaging the PTGFR receptor [17].…”
Section: Discussionmentioning
confidence: 99%